Experimentally determined effects of olivine crystallization and melt titanium content on iron isotopic fractionation in planetary basalts. (1st October 2018) - Prissel, Kelsey B.; Krawczynski, Michael J.; Nie, Nicole X.; Dauphas, Nicolas; Couvy, Hélène; Hu, Michael Y.; Alp, E. Ercan; Roskosz, Mathieu
Abstract: Olivine is the most abundant mantle mineral at depths relevant to oceanic crust production through melting. It is also a liquidus phase for a wide range of mafic and ultramafic magma compositions. We have experimentally investigated the effects of olivine crystallization and melt composition on the fractionation of Fe isotopes in igneous systems. To test whether there is a melt compositional control on Fe isotopic fractionation, we have conducted nuclear resonant inelastic X-ray scattering (NRIXS) measurements on a suite of synthetic glasses ranging from 0.4 to 16.3 wt.% TiO2 . The resulting force constants are similar to those of the reduced ( f O2  = IW) terrestrial basalt, andesite, and dacite glasses reported by Dauphas et al. (2014), indicating that there is no measurable effect of titanium composition on Fe isotopic fractionation in the investigated compositional range. We have also conducted olivine crystallization experiments and analyzed the Fe isotopic composition of the experimental olivines and glasses using solution MC-ICPMS. Olivine and glass separates from a given experimental charge have the same iron isotopic composition within error. This result is robust in both the high-Ti glass (Apollo 14 black) and low-Ti glass (Apollo 14 VLT) compositions, and at the two oxygen fugacities investigated (IW−1, IW+2). Additionally, we have determined that Fe loss in reducing one-atmosphere gas-mixing experiments occurs not only as loss to the Re wire container, but also as evaporative loss, and each mechanism of experimental Fe loss has an associated Fe isotopic fractionation. We apply our results to interpreting Fe isotopic variations in the lunar mare basalts and lunar dunite 72415-8. Our experimental results indicate that neither melt TiO2 composition nor equilibrium olivine crystallization can explain the observed difference in the iron isotopic composition of the lunar mare basalts. Additionally, equilibrium iron isotopic fractionation between olivine and melt cannot account for the "light" iron isotopic composition of lunar dunite 72415-8, unless the melt from which it is crystallizing was already enriched in light iron isotopes. Our results support models of diffusive fractionation to explain the light iron isotopic compositions measured in olivine from a variety of rock types and reduced ( f O2  = IW−1 to IW+2) igneous environments (e.g., lunar dunite and basalts, terrestrial peridotites and basalts, martian shergottites).